A model of self-regulation in preventing risk sexual behavior among adolescents - Lestari, Wahyu Agustin Eka; Indarwati, Retno; Krisnana, Ilya; Sudarsiwi, Neisya Pratiwindya (Intelektual Pustaka Media Utama, 2023)
The inability to control themselves causes adolescents to have low self- regulation and causes engage in risky sexual behavior which can cause serious problems such as sexually transmitted diseases, disability, and death. This study aims to develop a self-regulation model based on the theory of planned behavior to prevent risky sexual behavior in adolescents. Explanatory observation with a cross-sectional approach to 140 adolescents in four high schools/vocational schools selected using a convinience sampling. Data collection used questionnaires, focus group discussion (FGD), and expert discussions. Data analysis using partial least square. The development of a self-regulation model based on the theory of planned behavior toward preventing risky sexual behavior in adolescents has the best path, namely the path from background factors (X1) to subjective norms (X3) to personal regulation (X6) and behavioral self-regulation (Y1). The direct effect shows that intention (X4) has a direct effect on self-regulation (Y1). Intention is an important domain for forming a behavior through attitudes, subjective norms, and behavioral control so that self-regulation will be formed to prevent risky sexual behavior in adolescents. Adolescents should be given the training to improve self-regulation to be able to take action to prevent risky sexual behavior.